Effects of tailored advice on injury prevention knowledge and behaviours in runners: Secondary analysis from a randomised controlled trial. (May 2019) - Hollman, Heather; Ezzat, Allison; Esculier, Jean-Francois; Gustafson, Paul; Scott, Alex
Abstract: Objectives: To determine whether biweekly tailored advice was more effective than general advice at baseline alone for enhancing evidence-based running-related injury (RRI) prevention knowledge and behaviours in runners. Design: Randomised controlled trial, blinded statistical analysis, secondary analysis. Setting: Recreational running clinics. Participants: Running clinics were cluster randomised into intervention or control groups. All participants (n = 51) received general RRI prevention advice (baseline), after which the intervention group (n = 31) received additional biweekly tailored advice (weeks 3–11), before all participants completed a Final Questionnaire (week 13). Main outcome measures: Between-group differences in change of evidence-based RRI prevention knowledge and behaviours. Results: Compared to baseline, the number of correct knowledge responses significantly increased in the intervention group (5.77, 95% CI 4.73, 6.81) and remained unchanged in controls (0.25, 95% CI -1.04, 1.55), outlining a positive effect only in the intervention group (p = 2.06 × 10 -8 ). The number of correct behaviour responses significantly increased in the intervention group (1.94, 95% CI 0.94, 2.93) however this increase was not significantly greater than controls (p = 0.075). Conclusions: Biweekly tailored advice improved RRI prevention knowledge in runners. Further research into the impact of knowledge and behavioural change on RRI occurrence is warranted. ISRCTN 17357362 Highlights: Tailored advice enhanced evidence-based running injury prevention knowledge. Tailored advice trended towards enhanced running injury prevention behaviours. Recreational runners experienced minimal barriers to practicing injury prevention interventions.